Pengaruh Lingkungan dan Masyarakat terhadap Penyakit Demam Berdarah di Desa Truko Kecamatan Kangkung Kendal - Farid Rizqi Ananda; Adita Rizki Kurniawati; Teresa Amelya Putri; Ariska Kurnia Rachmawati (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
One of the health problems in society that still occurs a lot is dengue fever. dengeu (DHF). This viral disease is usually transmitted through the bite of the mosquitoes Aedes aegypti and Aedes albopictus. Until now, dengue fever disease has not yet been controlled, preventive programs in the community have also not been preventive programs in the community have also not been fully realized because the outbreak of this disease is increasingly showing high high numbers. Dengue fever is strongly influenced by environmental factors. Environment. An unhealthy and contaminated environment is very prone to the occurrence of various diseases including dengue fever. Other than that social factors can also affect human health such as economic conditions, education, and government policies. This activity was carried out on date in Truko Village, Kangkung Sub-district, Kendal Regency. The form of This activity is an action to prevent and break the chain of the spread of dengue fever in the spread of dengue fever in the Truko village area